PENGARUH TEKNOLOGI BUDIDAYA YANG BERBEDA TERHADAP KUALITAS AIR PADA TAMBAK UDANG INTENSIF - Sartika Tangguda; M. Fadjar; Ellana Sanoesi (Universitas Sriwijaya, 2018)
ABSTRACT The purpose of this research was to know the influence of different shrimp farming technology on water quality (ammonia, nitrite, and nitrate) and survival rate. The method that used in this research was experimental method. Retrieval of data was obtained from three locations of vaname shrimp farming in Tuban, East Java, were in Bancar, Bancar (biofloc technology), Tasikmadu, Palang (semi biofloc technology), and Keradenan, Palang (plankton technology). The main parameters were the value of ammonia, nitrite, and nitrate, while the supporting parameters were the water quality (temperature, pH, DO, salinity, and transparency), production, and survival rate. The results showed that average of ammonia value in biofloc, semi biofloc, and plankton ponds were 0,037 – 0,044 ppm; 0,011 – 0,015 ppm; and 0,023 – 0,026 ppm, respectively. The average of nitrite value in biofloc, semi biofloc, and plankton ponds were 0,128 – 0,0135 ppm; 0,075 – 0,112 ppm; dan 0,030 – 0,039 ppm, respectively. The average of nitrate value in biofloc, semi biofloc, and plankton ponds were 1,231 – 1,414 ppm; 0,667 – 0,704 ppm; dan 0,883 – 0,980 ppm, respectively. The water quality in each pond (biofloc, semi biofloc, and plankton) in which temperature (27 – 32oC), pH (6,5 – 8,2), DO (4,65 – 7,35 ppm), salinity (1 – 39 ppt), transparency (20 – 35 cm). The production of vaname shrimp in biofloc pond was 20,78 – 26,28 ton/ha; semi biofloc was 14,83 – 20,29 ton/ha; and plankton was 7,49 – 9,25 ton/ha. The average of survival rate in biofloc, semi biofloc, and plankton ponds were 82,74%; 72,92%; dan 80,62%, respectively. From this research we could summarized that farming technology influenced on water quality (ammonia, nitrite, and nitrate), and the biofloc technology gave the best influence on water quality furthermore would influence survival rate of vaname shrimp. Keywords: vaname shrimp, water quality, survival rate, biofloc